Vibration Attenuation On Vacuum Cleaner By Rubber Mount - Yeoh, Sze Chee (Universiti Sains Malaysia, 2018)
Noise produced by a household vacuum cleaner is generally built of airborne and structure-borne noise. Isolation of vibration transmitted from the electric motor blower of a vacuum cleaner to the other part of vacuum cleaner also can reduce the transmission of noise. To attenuate the vibration magnitude of household vacuum cleaner, a rubber mounting system is implemented onto the motor housing assembly. Thus, modal analysis is carried out to identify the structural characteristic of electric motor blower and vacuum cleaner. Furthermore, dynamic properties such as loss factor and frequency dependent stiffness are the important parameters to select the most suitable rubber mount. Thus, impact testing is carried out to obtain the receptance function of each individual rubber mount. As the interest is to decrease vertical and horizontal acceleration, a rubber mounting system is proposed onto the motor housing assembly with a suitable rubber mount based on its dynamic characteristics. There are three configurations to study the effectiveness of rubber mounting technique in reducing vibration magnitude. In result, for configuration A, the horizontal acceleration is decreased by 7.06% while vertical acceleration is reduced by 22.99%. Following with configuration B, the horizontal acceleration is reduced by 28.66% while vertical acceleration is dropped by 20.55%. Last but not the least, for configuration C, horizontal and vertical acceleration are reduced by 36.33% and 14.33% respectively. In short, the vibration magnitude of vacuum cleaner is effectively reduced in both horizontal and vertical directions. Hence, the proposed rubber mounting is an appropriate method in reducing the vibration transmitted from the electric motor blower.